Multidisciplinary perspectives on human capital and information technology professionals - Ahuja, Vandana; Rathore, Shubhangini, 1986- (Information Science Reference, 2018)
"This book focuses on the IT field from the outlook of industry professionals and covers multidisciplinary themes such as human resource management, sociology, psychology, and management along with technology itself. It emphasizes articles linking theory with application or critically analyzing cases with the objective of identifying good practice in the management of IT human capital"--